An Unusual Hybrid Salivary Gland Tumor: Molecular Analysis Informs the Potential Pathogenesis of This Rare Neoplasm - Yan Zhou; Ernesto Martinez Duarte; David J. Eleff; Laura J. Tafe; Jason M. Leibowitz; Darcy A. Kerr (Hindawi Limited, 2019)
Background. The presence of two or more tumor entities growing in adjacent locations within the salivary gland is very rare, and pathologic studies on such lesions are limited, particularly those with molecular information. Since the clinical history and imaging studies are usually nonspecific, accurate diagnosis and clinical management largely depend on a thorough histological examination. Methods and Results. We describe a 71-year-old man with an unusual case of hybrid salivary gland tumor composed of mucoepidermoid carcinoma and basal cell adenoma. Molecular analysis revealed differing driver genetic alterations in each component. Conclusions. Hybrid salivary gland tumors are rare, and their pathogenesis is controversial. The combination of mucoepidermoid carcinoma and basal cell adenoma has not been previously described. While malignant transformation of adenoma to carcinoma seems plausible, gene sequencing was more suggestive of their independent derivation. Key to appropriate surgical management is identifying the more aggressive component, ideally at the time of intraoperative consultation.